Strengthening Rasch Modeling for Objective and Fair Assessment for Chemistry Teachers - Suwahono Suwahono (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The competence of a good chemistry teacher will contribute to a fair assessment ability. This service aims to improve the professional competence of the sub-field of assessment for chemistry teachers at madrasahs in the Mranggen sub-district. This service is participatory by processing the results in a quantitative descriptive manner with one variable, namely the professional competence of the teacher's assessment. Service Locations in Madrasahs, Mranggen District. The number of participants in this service is 20 active chemistry teachers. Data collection techniques using closed and open questionnaires. Data validity uses content validity. Data reliability using Croncbach's Alpha technique. Data analysis techniques use the percentage formula to determine the achievement of each component through statistical data. The results of Community Service found that the professional competence of chemistry teachers at madrasas in the Mranggen sub-district was on average in the very good category, but variations in the use of assessment software were very lacking and had never been carried out. The service contribution gives a good value for changes in the ability to use the Rasch model assessment software after the service is over, but this depends on the amount of motivation the participants have.